PENGARUH PERTUMBUHAN EKONOMI DAN KEMISKINAN TERHADAP IPM 14 KABUPATEN KATEGORI “SEDANG” DI PROVINSI JAWA TIMUR - Mayang Dwi Pitaloka; P.S Prabowo (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This study aims to see the significant influence of Economic Growth and Poverty on the Human Development Index (HDI) of 14 districts with the